Influence of Product Quality and Price on Purchase Decision (Case Study on Consumers in Bumi Rempah Padalarang UMKM, West Bandung District) - Natasya Fadilla Rahmatunnisa; Ayi Muhiban (International Journal of Integrative Sciences, 2023)
This study was conducted on consumers in the Bumi Rempah UMKM, Padalarang, West Bandung Regency. The purpose of this study is to find out how much the influence of product quality and price contributes on purchasing decisions both partially and simultaneously at Bumi Rempah UMKM. The research method used in this research is descriptive, and associative method. The unit of analysis in this study is the individual, namely consumers in Bumi Rempah UMKM. This study's sample size was 64 respondents. Multiple linear regression analysis was employed as the analytical method, and the validity and reliability of the research instruments were also tested. Based on the study's results, the independent variables (product quality and price) have a considerable influence on the dependent variable (buying choice) both partially and simultaneously. he implication of this study is that Bumi Rempah owners must review the packaging used to make it safer and easier for consumers, adjust prices with the benefits that consumers get so that consumers feel more satisfied, review the factors that contribute to low purchasing decisions on the ShopeeFood app, so that product quality can be enhanced and improved by always using fresh raw ingredients and a consistent taste